Types of Literature in the Book of Mormon: Historical Narrative, Memoir, Prophetic Discourse, Oratory - Sperry, Sidney B. (Journal of Book of Mormon studies, 1995)
Historical narrative in the Book of Mormon is written by laymen, and is the truth as they see it. Of emphasis is the doctrine that blessings follow those who keep the commandments; they will prosper in the land. More than autobiography, the words of the writers could be described as memoirs. Benjamin delivered a wonderful oration which deserves detailed study, and which can be divided into three parts.